Enhancement of the solubility of polyaniline and studying the optical properties of (PANI+PVA) polymers blends. - Hassan, Nadia M. (Iraqi Journal of Physics, 2019)
The optical transmission and UV-VIS absorption spectra have been recorded in the wavelength range (200-1100m) for different composition of polyaniline and polyvinyl Alcohol(PVA ) blends thin films. Polyaniline was prepared in acidic medium to enhancement the solubility and processibility, The optical energy gap (Eopt) refractive index and optical dielectric constant real and imaginary part have been evaluated. The effects of doping percentage of prepared polyaniline on these parameters was discussed and the non –linear behavior for all these parameters was investigated.